In Situ Enzyme Immobilization with Oxygen‐Sensitive Luminescent Metal–Organic Frameworks to Realize "All‐in‐One" Multifunctions. Issue 21 (8th March 2019) - Xu, Yuzhi; Liu, Si‐Yang; Liu, Junling; Zhang, Li; Chen, Danping; Chen, Jun; Ma, Yingjun; Zhang, Jie‐Peng; Dai, Zong; Zou, Xiaoyong
Abstract: Metal–organic frameworks (MOFs) for enzyme immobilization have already shown superior tunable and designable characteristics, however, their diverse responsive properties have rarely been exploited. In this work we integrated a responsive MOF into a MOF–enzyme composite with the purpose of designing an "all‐in‐one" multifunctional composite with catalytic and luminescence functions incorporated into a single particle. As a proof‐of‐concept, glucose oxidase (GOx) was encapsulated in situ within an oxygen (O2 )‐sensitive, noble‐metal‐free, luminescent Cu I triazolate framework (MAF‐2), denoted as GOx@MAF‐2. Owing to the rigid scaffold of MAF‐2 and confinement effect, the GOx@MAF‐2 composite showed significantly improved stability (shelf life of 60 days and heat resistance up to 80 °C) as well as good selectivity and recyclability. More importantly, owing to the O2 sensitivity of MAF‐2, the GOx@MAF‐2 composite exhibited a rapid and reversible response towards dissolved O2, thereby allowing direct and ratiometric sensing of glucose without the need for chromogenic substrates, cascade enzymatic reactions, or electrode systems. High sensitivity with a detection limit of 1.4 μm glucose was achieved, and the glucose levels in human sera were accurately determined. This strategy has led to a new application for MOFs that can be facilely extended to other MOF–enzyme composites due to the multifunctionality of MOFs. Abstract : Multifunctional composite : The "all‐in‐one" MOF–enzyme composite prepared in this work utilizes MAF‐2 simultaneously as protective matrix and signal transducer and can be applied to the detection of glucose in human serum (see figure). Glucose oxidase (GOx) is encapsulated within the MAF‐2 matrix, and the rapid and reversible response of the latter towards dissolved O2 allows the sensing of glucose. The composite shows good stability, selectivity, and recyclability.